2016
DOI: 10.1016/j.celrep.2016.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of IL-11 and Apical Redirection of gp130 Is Mediated by IL-11α Receptor

Abstract: Interleukin (IL)-11 signaling is involved in various processes, including epithelial intestinal cell regeneration and embryo implantation. IL-11 signaling is initiated upon binding of IL-11 to IL-11R1 or IL-11R2, two IL-11α-receptor splice variants, and gp130. Here, we show that IL-11 signaling via IL-11R1/2:gp130 complexes occurs on both the apical and basolateral sides of polarized cells, whereas IL-6 signaling via IL-6R:gp130 complexes is restricted to the basolateral side. We show that basolaterally suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The main producers of IL-6 and IL-22 are immune cells, which are enriched in lamina propria and are in close proximity to the basolateral epithelial membrane. Intestinally, many cytokine receptors are expressed on the basolateral surface of polarized epithelial cells (64). Therefore, a rapid and robust response to cytokines such as IL-6 and IL-22 at the basolateral surface appears to be an important mechanism enabling IECs to sense and act quickly to the changing levels of cytokines in the adjacent environment, potentially leading to protective responses.…”
Section: Discussionmentioning
confidence: 99%
“…The main producers of IL-6 and IL-22 are immune cells, which are enriched in lamina propria and are in close proximity to the basolateral epithelial membrane. Intestinally, many cytokine receptors are expressed on the basolateral surface of polarized epithelial cells (64). Therefore, a rapid and robust response to cytokines such as IL-6 and IL-22 at the basolateral surface appears to be an important mechanism enabling IECs to sense and act quickly to the changing levels of cytokines in the adjacent environment, potentially leading to protective responses.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium for Ba/F3-gp130 additionally contained 10 ng/ml Hyper-IL-6 which was expressed and purified as described in [31]. After stable transduction Ba/F3-gp130 IL-11R variant cells were cultured with 10 ng/ml recombinant IL-11 instead of Hyper-IL-6, and IL-11 was produced as described [18, 32]. The anti-IL-11R pAb N-20 was obtained from Santa Cruz Biotechnology (Santa Cruz, CA, USA), the anti-GAPDH mAb, anti-myc-tag mAb, anti-pSTAT3 and anti-STAT3 mAb were from Cell Signaling (Frankfurt/M, Germany) and the anti-GM130 mAb was from BD Bioscience.…”
Section: Methodsmentioning
confidence: 99%
“…Upon ligand binding, which is facilitated by the so-called cytokine-binding module located in D2/D3, a homodimer of the common β-receptor of the IL-6 family, glycoprotein (gp)130, is recruited, and intracellular signaling cascades, among them the Janus kinase/Signal Transducer and Activator of Transcription (Jak/STAT) pathway, are activated [7, 17]. In polarized cells, the IL-11R localizes to apical and basolateral membranes and has transcytotic activity [18]. We have recently shown that the IL-11R can undergo limited proteolysis, predominantly by the metalloprotease ADAM10, and that the resulting soluble IL-11R (sIL-11R) can form an agonistic complex with its ligand IL-11 that is able to activate cells irrespective of their own IL-11R expression [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the IL-11R determines which cells can be activated by the cytokine, while gp130 is expressed ubiquitously. The IL-11R is expressed on a variety of different cell types and tissues, including intestine, spleen, heart, and lung (Davidson et al, 1997;Putoczki and Ernst, 2010) and acts as a transcytosis receptor for IL-11 on polarized cells (Monhasery et al, 2016). Importantly, the IL-11R is also found on osteoblasts, and signaling via the IL-11R is required for normal bone remodeling in mice.…”
Section: Introductionmentioning
confidence: 99%